CARICOM universal standard of care handbook for the treatment and rehabilitation of drug dependance : guidelines and criteria for the assessment of standards of care in the treatment of drug dependance (Caribbean Community Secretariat GeorgetownGY, 2011)
Provides basic guidelines and criteria for the development of a minimum set of standards for the care and treatment of drug dependence in the CARICOM region. Includes recommendations from CARICOM demand reduction experts.
Available in print and CDRom versions